1993
DOI: 10.1093/ajcn/57.4.566
|View full text |Cite
|
Sign up to set email alerts
|

A physiological amount of zinc supplementation: effects on nutritional, lipid, and thymic status in an elderly population

Abstract: Forty-four institutionalized elderly subjects with body mass indexes (BMI) of either > or = 24 or < or = 21 participated in a 16-wk crossover study designed to determine the effects of low-dose zinc supplementation [306 mumol (20 mg)/d] on food intake, anthropometry, and biochemical and immunological indexes. Initial serum zinc concentrations were low in both groups and increased by approximately 20% after zinc supplementation. Zinc supplementation allowed a partial but significant restoration of serum thymuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0
2

Year Published

1999
1999
2011
2011

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(49 citation statements)
references
References 32 publications
3
44
0
2
Order By: Relevance
“…Male Balb/c 50 (C) 18 mg as zinc sulphate Increased mean survival (40) 50 (Z) C57Bl/6 mice 8 (C) 300 mg/kg of Zn for 25 d Improved thymic output (47) 8 (Z) Table 1) in the majority of the studies, Prasad et al (49) and Boukaiba et al (50) have found an increment of thymulin activity and improvement in response to skin-test antigens and taste acuity; Bogden et al (51) have reported some benefit exclusively for increased lymphocyte mitogen proliferative response; Cakman et al (52) have found enhanced IFN-g production by leucocytes; Fortes et al (53) report an increased number of cytotoxic T lymphocytes; Hodkinson et al (54) describe no effect on some markers of immunity (natural killer cells) or inflammation (C-reactive protein), but only increased the ratio of CD4/CD8 T lymphocytes at month 6; Kahmann et al (55) report reduced levels of activated T-cells and basal IL-6 release from peripheral blood mononuclear cells and improved T-cell response. Using higher doses of zinc, 40-220 mg/d with different lengths of treatment (Table 1), Duchateau et al (56) and Sandstead et al (57) have observed an improvement in response to skin-test antigens and taste acuity; an improved delayed type hypersensitivity reaction has been also found in a limited number of subjects by Cossack (58) and by Wagner et al (59) ; Prasad et al (60) found improved IL-2 mRNA.…”
Section: (Z)mentioning
confidence: 99%
“…Male Balb/c 50 (C) 18 mg as zinc sulphate Increased mean survival (40) 50 (Z) C57Bl/6 mice 8 (C) 300 mg/kg of Zn for 25 d Improved thymic output (47) 8 (Z) Table 1) in the majority of the studies, Prasad et al (49) and Boukaiba et al (50) have found an increment of thymulin activity and improvement in response to skin-test antigens and taste acuity; Bogden et al (51) have reported some benefit exclusively for increased lymphocyte mitogen proliferative response; Cakman et al (52) have found enhanced IFN-g production by leucocytes; Fortes et al (53) report an increased number of cytotoxic T lymphocytes; Hodkinson et al (54) describe no effect on some markers of immunity (natural killer cells) or inflammation (C-reactive protein), but only increased the ratio of CD4/CD8 T lymphocytes at month 6; Kahmann et al (55) report reduced levels of activated T-cells and basal IL-6 release from peripheral blood mononuclear cells and improved T-cell response. Using higher doses of zinc, 40-220 mg/d with different lengths of treatment (Table 1), Duchateau et al (56) and Sandstead et al (57) have observed an improvement in response to skin-test antigens and taste acuity; an improved delayed type hypersensitivity reaction has been also found in a limited number of subjects by Cossack (58) and by Wagner et al (59) ; Prasad et al (60) found improved IL-2 mRNA.…”
Section: (Z)mentioning
confidence: 99%
“…Studies using low-dose supplementation of zinc alone (Boukaiba et al, 1993) or zinc associated with selenium (Girodon et al, 1999) in elderly patients, provide a significant improvement in thymic function and antibody response, respectively, after vaccination. These results suggest that these nutrients play a beneficial role, and, more particularly, that zinc improves an elderly person's resistance to infections, thereby increasing his or her immunity.…”
Section: Impact Of Zinc and Other Trace Element Supplementation In Thmentioning
confidence: 99%
“…Pharmacological Zn 2+ supplementation is not only able to restore an impaired immune response but also improve normal immune function by raising the physiological Zn 2+ serum level of 8 ± 12 mM about 10-fold to 100 mM. 11 Higher concentrations of extracellular Zn 2+ (500 ± 1000 mM) have frequently been used to block apoptosis in a variety of systems. Surprisingly, lower and more physiological concentrations of Zn 2+ (80 ± 200 mM) can induce partial death in thymocytes.…”
Section: Introductionmentioning
confidence: 99%